THE EFFECT OF COLOURING PICTURES TREATMENT ON ANXIETY IN PRE-SCHOOL AGE PATIENT HOSPITALIZED AT BALADHIKA HUSADA HOSPITAL JEMBER - Fika Indah Prasetya (UPT Penerbitan Universitas Jember, 2020)
Background: The development of pre-school age children can not be separated from playing and learning. Pre-school age children play with all their emotions, feeling, and thoughts. When a child must be hospitalized, it can disturb the child’s playing or learning needs. These changes have an impact on anxiety levels in children. Purpose: This research aims to identify the effect of coloring pictures on anxiety levels in pre-school aged children who were hositalized. Methods: The research designed usedwas a pretest-posttest with control group. The respondent included 10 children and the quota sampling was used as sampling method. Data analysis used paired t-test. Result: The research showed a p value of 0.000<0.05, which means that there was an effect on coloring pictures to the anxiety level of children who are treated in hospital. Conclusion: Coloring picture could reduce anxiety levels in children who were hospitalized. For suggestion, hospital management needs to modify the policy in order to fulfill the need of playing and learning while the child is hospitalized so that the child does not experience anxiety, for example comfortable room environment for children Key words: Coloring pictures, Patient, Anxiety